Analytical Method Development and Validation for the Quantification of Acetone and Isopropyl Alcohol in the Tartaric Acid Base Pellets of Dipyridamole Modified Release Capsules by Using Headspace Gas Chromatographic Technique - Sriram Valavala; Nareshvarma Seelam; Subbaiah Tondepu; V. Shanmukha Kumar Jagarlapudi; Vivekanandan Sundarmurthy (Journal of Analytical Methods in Chemistry)
A simple, sensitive, accurate, robust headspace gas chromatographic method was developed for the quantitative determination of acetone and isopropyl alcohol in tartaric acid-based pellets of dipyridamole modified release capsules. The residual solvents acetone and isopropyl alcohol were used in the manufacturing process of the tartaric acid-based pellets of dipyridamole modified release capsules by considering the solubility of the dipyridamole and excipients in the different manufacturing stages. The method was developed and optimized by using fused silica DB-624 (30 m × 0.32 mm × 1.8 µm) column with the flame ionization detector. The method validation was carried out with regard to the guidelines for validation of analytical procedures Q2 demanded by the International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use (ICH). All the validation characteristics were meeting the acceptance criteria. Hence, the developed and validated method can be applied for the intended routine analysis.